Quantitative estimates of organic carbon contributions to the river-estuary-marine system in the Jiaozhou Bay, China - Ke Liu; Xiaotong Xiao; Daolai Zhang; Yang Ding; Li Li; Meixun Zhao (Ecological Indicators, 2021)
Land-ocean interactions play an important role in transporting and accumulating organic carbon (OC) in marine sediments. Understanding sources (terrestrial, marine and anthropogenic contributions) of sedimentary OC are important to better evaluate the processes controlling the OC distribution in coastal zones. In this study, we present bulk parameters of total organic carbon (TOC), total nitrogen (TN), stable carbon isotopic composition (δ13Corg) and biomarker contents in surface sediments from the Dagu River-estuary-marine system in the Jiaozhou Bay. Comparison between OC/N ratios and δ13Corg indicated significant C4 plant contribution to the sedimentary OC, which was approximately equal to C3 plant contribution in this study. Generally, terrestrial biomarkers contents were high in the river and showed a decreasing trend towards the estuary and inner bay. Marine biomarkers displayed opposite spatial distribution patterns with terrestrial biomarkers except for the brassicasterol that also has a terrestrial/fluvial source. The universal detection of petroleum and sewage biomarkers revealed the significant anthropogenic influence on the sedimentary OC in our study. Principal component analysis-multiple linear regression (PCA-MLR) was performed to quantitatively estimate the OC contributions in the Jiaozhou Bay, showing that anthropogenic activities contributed 77.6% and 29.9% to the sedimentary OC in Dagu River and outside the Dagu River (the estuary and the inner Bay), respectively. Further studies need to be carried out to test this approach in broader regions.